The Potency of Kirinyuh (Chromolaena odorata L.) and Kemangi leaf (Ocimum basilicum) as Biopesticide against Schizophyllum commune Fries - Farah Diba; Ulvatur Rochmawati Nauli; Wiwik Winarsih; H A Oramahi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Schizophyllum communeÃÂ Fries is a wood rot fungus that attacks living trees and wood products which causes high economic losses. The research objective was to evaluate the extracts of kirinyuh (Chromolaena odorataÃÂ L) and kemangi (Ocimum basilicumÃÂ L) as a biopesticide to controlÃÂ Schizophyllum communeÃÂ Fries. The solvents used for extracting the leaves of Kirinyuh and kemangi were 96% ethanol solvent in a ratio of 1: 3 (w/v). The extracts then formed into 2%, 4%, 6%, 8%, and 10% concentration and mixed into PDA medium. The media was poured into a petri dish and then kept in incubator room. Then the isolates ofÃÂ Schizophyllum communeÃÂ Fries fungus, seven days old with a five mm diameter, were put in the medium center. The parameter test was the value inhibition the fungal growth, comparing control treatment and the given concentration treatment. The results of research showed that kirinyuh leaf extract at a concentration of 2% has strong antifungal values with growth inhibition of 74.25%, at concentration 4%, 6%, 8%, and 10% had a strong antifungal value with growth inhibition of 82.97%; 88.90%; 89.49% and 91.67%. Extracts of kemangi leaf had strong antifungal values (at concentration 2% and 4%) with growth inhibition of 66.63% and 71.72%, while at concentration 6%, 8%, and 10% had a strong antifungal value with inhibition of fungal growth by 81.05%; 83.02%; and 100%. The bioactive compounds found in kemangi leaf extracts were saponins, flavonoids, and linalool which are toxic and kill fungi. Kirinyuh leaf extract has an active alkaloid compound that is toxic and inhibits the formation of fungal cell walls. The optimal concentration of kemangi extract to inhibit the growth of Schizophyllum communeÃÂ was 6% and from kirinyuh extract was 4%.ÃÂ